2017
DOI: 10.1111/nph.14675
|View full text |Cite
|
Sign up to set email alerts
|

PhERF6, interacting with EOBI, negatively regulates fragrance biosynthesis in petunia flowers

Abstract: In petunia, the production of volatile benzenoids/phenylpropanoids determines floral aroma, highly regulated by development, rhythm and ethylene. Previous studies identified several R2R3-type MYB trans-factors as positive regulators of scent biosynthesis in petunia flowers. Ethylene response factors (ERFs) have been shown to take part in the signal transduction of hormones, and regulation of metabolism and development processes in various plant species. Using virus-induced gene silencing technology, a negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 64 publications
0
32
0
Order By: Relevance
“…To identify the function of the PaACLA1-A2 and PaACLB1-B2 genes, vectors were constructed to suppress the expression of these genes because we had already established a highly efficient VIGS system in petunia ‘Ultra’ ( Tan et al , 2014 ; Liu et al ., 2017 ). Approximately 30 days after petunia seedlings were infected, no visible change was observed in any single-gene-silenced plants compared with the controls.…”
Section: Resultsmentioning
confidence: 99%
“…To identify the function of the PaACLA1-A2 and PaACLB1-B2 genes, vectors were constructed to suppress the expression of these genes because we had already established a highly efficient VIGS system in petunia ‘Ultra’ ( Tan et al , 2014 ; Liu et al ., 2017 ). Approximately 30 days after petunia seedlings were infected, no visible change was observed in any single-gene-silenced plants compared with the controls.…”
Section: Resultsmentioning
confidence: 99%
“…Recent research has provided evidence for interactions between AP2/ERF and MYB transcription factors in regulating other aspects of fruit quality, including texture (EjAP2-1 and EjMYB; Zeng et al, 2015) and color (PyERF3 and PyMYB114; Yao et al, 2017). A group VIII ERF also was shown recently to interact with an MYB to regulate floral scent production in petunia (Liu et al, 2017). In strawberry fruit, DOF, in combination with an MYB, has been reported to be involved in the regulation of eugenol production, and the identification of this second transcription factor (DOF) suggests that it is a good target in breeding for improved flavor (Molina-Hidalgo et al, 2017;Tieman, 2017).…”
Section: A Faerf#9 and Famyb98 Complex Is Involved In Regulating Faqrmentioning
confidence: 99%
“…After 16–24 h, accumulation of the PhDHS-GFP fusion protein was detected in the cytoplasm and nucleus of petunia protoplasts (Figure 2A,B). To further verify the fluorescence signal of PhDHS-GFP fusion protein in the nucleus, we use EOBII-RFP (red fluorescent protein) as a nuclear marker given that it was previously demonstrated that EOBI are nuclear-localized MYB factors (Spitzer-Rimon et al, 2010, 2012; Liu et al, 2017). Localization of the PhDHS-GFP fusion protein was determined by visualization with a fluorescence microscope.…”
Section: Resultsmentioning
confidence: 99%